Critical Theory of Herbert Marcuse (An Attempt to Criticize the Practices of Technological Rationality in the Advanced Industrial Society): Analytical- Critical Study - Fayad, Hossam Aldin Mahmoud (Journal of Humanities & Social Sciences, 2022)
The aim of the research is to clarify the mechanism of technological rationality practices in containing the opposition and consolidating the manifestations of cultural alienation and controlling all human dimensions in the advanced industrial society, in addition to identifying the negative effects of it on the human and social reality in the advanced industrial society, based on the theoretical and methodological foundations of critical theory when Herbert Marcuse. The research relied on the analytical- critical method in the study, analysis, interpretation and criticism of the research topic. The research also reached a set of results, the most important of which is that the advanced industrial society was able to master and master, through the practices of technological rationality (instrumental), to control and control the joints of all social life by establishing a certain pattern of human relations characterized as one- dimensional, but Marcuse did not present to us Realistic solutions to get out of the net of those practices rooted in the nature of the social construction of an advanced industrial society. In the end, the research recommended the necessity of rational rationalization with a human dimension for the use of technological means in social life as auxiliary tools to make social life simpler and easier away from control, control and oppression and reducing social reality to the instrumental dimension of technological rationality, in addition to calling on those working in the fields of social sciences to do more There are studies and research on the danger of technology controlling all aspects of social life through the excessive use of it without awareness commensurate with its continuously growing capabilities.
Keywords: theory; practices; technological rationality; industrial society